ANALISIS PERAN PERMODALAN NASIONAL MADANI (PNM MEKAAR SYARIAH) DALAM MENINGKATKAN PENDAPATAN MENURUT PERSPEKTIF EKONOMI ISLAM (Studi Kasus Pelaku Usaha Mikro di Nagari Abai Siat Kecamatan Koto Besar Kabupaten Dharmasraya) - Karen Elya Zikra; Zuwardi (CV. Adiba Aisha Amira, 2023)
This research is motivated by researchers' observations regarding the analysis of the role of civil national capital (PNM Mekaar Syariah) in increasing income according to an Islamic economic perspective for micro business actors in Nagari Abai Siat. This study aims to find out how the role of PNM Mekaar Syariah in increasing the income of micro-entrepreneurs. This research is a type of qualitative research that is descriptive in nature. Data collection techniques used are observation, interviews and documentation. While the data analysis techniques used are data reduction, data presentation, and drawing conclusions. From the results of the research conducted by the researchers, it was concluded that PNM Mekaar Syariah has helped increase the business income of micro-entrepreneurs in Nagari Abai Siat, Koto Besar District, Dharmasraya Regency. After getting capital from PNM Mekaar, micro entrepreneurs can increase their business so that the income they get increases. Of all these principles PNM Mekaar Syariah has implemented these principles and has not violated them, customers from PNM Mekaar do not feel abused and burdened by margins and PNM Mekaar employees also have an honest, fair and disciplined attitude